Coping with obesity in Primary Health Care under the National Food and Nutrition Policy: reflections based on the construction of a logical model (Research, Society and Development, 2021)
This article aimed to build a logical model for dealing with obesity in Primary Health Care based on the guidelines of the National Food and Nutrition Policy and, based on it, to identify potentialities and challenges in the management of this disease in practice in the literature. The logical model was built after a critical reading of the National Food and Nutrition Policy to identify activities specifically aimed at combating obesity, as well as projecting its possible effects. After the elaboration of the logical model, the analysis of articles identified through a review of the literature in the SciELO, BVS and LILACS databases was carried out, in addition to documentary research, in order to identify the potential and challenges of these strategies when evaluated in practice. The schematization of activities encouraged by the National Food and Nutrition Policy in the logical model showed that these actions can be important allies for reducing the impacts of obesity. However, it was identified in the literature that the activities indicated in the model, Food and Nutritional Surveillance, Permanent Health Education, matrix support and extended clinic, and creation of healthy environments, are still not satisfactorily carried out in practice, among other factors, due to the poor training of professionals, reduced number of health professionals, in addition to the lack of funding and incentives from the government. In general, more studies are needed to assess the actions carried out in Primary Health Care specifically to tackle obesity.